RETRACTED: Mapping the nexus between digital transformation and the green brand in the context of achieving SDGs - Us Yana; Pimonenko Tetyana; Lyulyov Oleksii; Kwilinski Aleksy (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 456, 00002 (2023), https://doi.org/10.1051/e3sconf/202345600002